2019
DOI: 10.3390/ijerph16142612
|View full text |Cite
|
Sign up to set email alerts
|

Addictive Features of Social Media/Messenger Platforms and Freemium Games against the Background of Psychological and Economic Theories

Abstract: Currently about 2.71 billion humans use a smartphone worldwide. Although smartphone technology has brought many advances, a growing number of scientists discuss potential detrimental effects due to excessive smartphone use. Of importance, the likely culprit to understand over-usage is not the smartphone itself, but the excessive use of applications installed on smartphones. As the current business model of many app-developers foresees an exchange of personal data for allowance to use an app, it is not surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 195 publications
(122 citation statements)
references
References 102 publications
2
116
0
4
Order By: Relevance
“…There are different SNSs used in China, among these are WeChat R , Weibo R , Qzone R , and QQ R (see also recent developments with the TikTok R platform showing huge growth rate in user numbers). The use of WeChat R has gained substantial popularity in China due to its multi-purpose character including payment functions and combining features of WhatsApp R and Facebook R (Gao and Zhang, 2013;Lien and Cao, 2014;Sampasa-Kanyinga and Hamilton, 2015;Montag et al, 2019a). According to statista.com, it has been reported that there are over one billion active WeChat R users (Statista.com, 2019) and it had reached 1.082 billion users by January 2019 (Weixin.qq.com., 2019), thereby showing the dramatic increase from the 300 million users in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…There are different SNSs used in China, among these are WeChat R , Weibo R , Qzone R , and QQ R (see also recent developments with the TikTok R platform showing huge growth rate in user numbers). The use of WeChat R has gained substantial popularity in China due to its multi-purpose character including payment functions and combining features of WhatsApp R and Facebook R (Gao and Zhang, 2013;Lien and Cao, 2014;Sampasa-Kanyinga and Hamilton, 2015;Montag et al, 2019a). According to statista.com, it has been reported that there are over one billion active WeChat R users (Statista.com, 2019) and it had reached 1.082 billion users by January 2019 (Weixin.qq.com., 2019), thereby showing the dramatic increase from the 300 million users in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of mobile applications are designed to prolong usage time leading to individual time distortion. Some scientists and technicians attempted to develop new techniques to measure and analyse smartphone addiction [90][91][92]. For example, Lin et al identified smartphone addiction via app-generated parameters, and the results suggested that recorded total usage time via app was significantly higher than self-reported usage time because of the time distortion effect [90].…”
Section: Discussionmentioning
confidence: 99%
“…However, Montag et al found that total length of weekly mobile phone usage in hours was overestimated and weekly outgoing calls were underestimated [91]. Furthermore, researchers reported that social media/messenger and freemium game applications were significant drivers of excessive smartphone usage; these applications could be much more addictive than traditional/classic computer/console games [92]. Hence, enterprises should seriously consider how to develop less addictive products and recognise what kinds of approaches facilitate use reduction and create the healthiest effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, mobile technologies provide users with unlimited content, which is increasingly tailored to their needs and preferences [26]. Importantly, the presentation of this content is frequently optimized to extend user time on site [27]. Third, the portability of mobile technologies allows for user interactions anywhere and at any time [28].…”
Section: Related Workmentioning
confidence: 99%